Cross-Border Trade In The Indonesia-Malaysia Border Area At The PLBN Aruk Of Sambas Regency - Yuliansyah; Muslimin H Kara; Rahman Ambo Masse; Sumar’in (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2025)
The export-import opportunities for various superior products from Sambas Regency through the Aruk PLBN are very high, especially with the presence of supporting government agencies and SOEs at the Aruk PLBN. So it is interesting to analyze further the cross-border trade in the Indonesia-Malaysia region in the Aruk PLBN area of Sambas Regency. This research is a type of field research that uses qualitative descriptive methods. The researcher tries to conduct an in-depth study by describing the phenomenon of cross-border trade that occurs at the Aruk Cross-Border Post. This will show the impact of the Aruk Cross-Border Post on the improvement of the Sambas Regency economy as a State Border Regency. At Aruk Cross-Border Checkpoint, cross-border trade activities are carried out in the Neutral Zone. This is because Malaysia still considers that cross-border trade is traditional trade, while the Indonesian government has recognized Aruk Cross-Border Checkpoint as an export and import crossing point. Currently, the obstacle to export-import faced at PLBN Aruk is the Indonesian government regulation regarding general exports. So PLBN Aruk only serves export activities while import activities still cannot be carried out. Furthermore, regarding the determination of Biawak status, Malaysia still considers it as traditional trade or only serving cross-border people. So that the export activities carried out by PLBN Aruk, the loading and unloading of goods is carried out at the zero point or Neutral zone. Trade transactions are still limited to raw agricultural and fishery commodities. The construction of the International Cargo Terminal facility has not been completed, and the port code for Aruk Cross-border Checkpoint has not been assigned, so it is not functioning as it should. Therefore, it is important to strive for Aruk Cross-border Checkpoint to be officially designated as an import-export gateway by the central government, so that Aruk Cross-border Checkpoint functions optimally.